PERAN PENDIDIK MEMBANGUN PERSAHABATAN SEJAK USIA DINI KUNCI RESILIENSI ANAK - Hamid Patilima (Program Studi Pendidikan Guru Anak Usia Dini, 2022)
Friendship is the main capital for every human individual, including early childhood. Friendship from an early age is largely determined by the role of educators, including fathers and mothers being the main ones. First and foremost educators as well as advanced educators provide space and opportunities for children to get to know each other and get to know fellow friends, without conditions. What about life today, does friendship get the attention of every educator? The full description of this article focuses on the study of friendship as a key to resilience. This study aims to build children's resilience from an early age through friendship.